Seragam Jadi Peluang: Implementasi Project Based Learning Sebagai Wadah Edupreneurship Siswa SMK Muhammadiyah Sumowono - Maesaroh, Siti; Akhirani, Shinta Tiresa; Pamuji, Eko; Miftakhudin, Miftakhudin; Kuat, Tri (Indo-MathEdu Intellectuals Journal, 2025)
The challenge of limited resources faced by vocational schools makes innovative learning strategies such as Project Based Learning (PjBL) a relevant alternative. This article aims to investigate the implementation of PjBL in the project of creating school uniforms as a means to instill edupreneurship values at Muhammadiyah Sumowono Vocational School. This research adopts a literature study approach. The data sources for this research are obtained from three main categories: textbooks, national and international scientific journal articles, and official policy documents. The data analysis techniques in this literature study are carried out through three main stages: concept classification, analysis of relationships between concepts, and synthesis. The results of the analysis show that vocational education in the era of digital disruption is required not only to produce graduates who are technically ready for work but also to possess an innovative and adaptive entrepreneurial spirit. The implementation of Project Based Learning (PjBL) in the form of a uniform manufacturing project has proven to be an effective medium for integrating productive learning with the instillation of entrepreneurial values. Through this activity, students are actively involved in the entire production process: from identifying needs, designing, calculating costs, to marketing strategies. This full involvement encourages the emergence of proactive attitudes, responsibility, creativity, teamwork, and the courage to take risks, all of which are essential elements in the entrepreneurial spirit.